TRADISI BARANTAM DALAM PERKAWINAN DI JORONG KAYU JAO NAGARI BATANG BARUS KECAMATAN GUNUNG TALANG KABUPATEN SOLOK MENURUT PERSPEKTIF AL-‘URF - Nazra Hafizatul Hasana; Yusnita Eva (Jurnal AL-AHKAM, 2020)
This research is motivated by the existence of the barantam tradition in a series of Walimatul al-Ursy events carried out by the people of Nagari Batang Barus. This tradition generally applies in Jorong  Kayu  Jao  which  has  been  passed  down  from  generation  to  generation  from  previous ancestors to the present. Initially this tradition existed because of the help of the ninik mamak and the  female  relatives  to  the  bride  but  over  time  this  changed  to  competition  and  competition  that was no longer healthy. The formulation of the problem in this study is how the background of the barantam  tradition  carried  out  by  the  Jorong  Kayu  Jao  Nagari  Batang  Barus  District  of  Gunung Talang District, Solok Regency and how the implementation of the barantam tradition carried out by  the  Jorong  Kayu  Jao  Nagari  Batang  Barus  community,  Gunung  Talang  District,  Solok  Regency according  to  the  perspective  of  Islamic  law  .  The  objectives  to  be  achieved  in  this  study  are  to explain  the  background  of  the  tradition  of  barantam  in  marriage  in  Jorong  Kayu  Jao  Nagari Batang  Barus,  Gunung  Talang  District,  Solok  Regency  and  to  know  the  Islamic  legal  view  of  the marriage  tradition  that  occurs  in  Jorong  Kayu Jao  Nagari  Batang  Barus,  Gunung  Talang District, Solok Regency. . This research is a field research (field research) using qualitative methods, which relies  on  data  collection  by  observation  and  interviews.  The  tradition of  barantam  carried  out  by the  people  of  Jorong  Kayu  Jao  Nagari  Batang  Barus,  Gunung  Talang  District,  Solok  Regency  is  a tradition that originates from their previous ancestors and is still preserved today. barantam is a ninik mamak, a relative, a woman who collects money at night after holding a Walimatul al-Ursy in the afternoon. For couples who do not practice the barantam tradition, the marriage is considered incomplete,  flawed  and  is  suspected  of  having  the  marriage  due  to  forbidden  acts  committed  by both  parties,  this  can  be  a  derivative  punishment  for  the  children  and  grandchildren  because  the parents'  marriages  are  not  cultic.  According  to  the  perspective  of  Islamic  law,  the  tradition  of barantam carried out by the community in Jorong Kayu Jao is not fully in accordance with Islamic law  because  there  are  still  elements  that  are  detrimental  to  the  parties  concerned.  There  is discrimination for those who do not commit and also a loss of sincerity for the parties involved in it. This  includes  "urf  fasid  if  it  is  maintained  without  repair  or  straightening  in  accordance  with syara".Keywords: Tradition, Barantam, al-'Urf